Efficacy and safety of canakinumab as a second line biologic after tocilizumab treatment failure in children with systemic juvenile idiopathic arthritis: A single-centre cohort study using routinely collected health data - Alexeeva, Ekaterina; Krekhova, Elizaveta; Dvoryakovskaya, Tatyana; Isaeva, Ksenia; Chomakhidze, Aleksandra; Chistyakova, Evgeniya; Lomakina, Olga; Denisova, Rina; Mamutova, Anna; Fetisova, Anna; Gautier, Marina; Vankova, Dariya; et al. (Frontiers in Pediatrics, 2023)
A significant number of systemic juvenile idiopathic arthritis (sJIA) patients discontinue biologic disease-modifying antirheumatic drugs (bDMARDs) for lack of efficacy or safety concerns. Studies of biologic therapy switch regimens in sJIA are required. Patients with sJIA who switched from tocilizumab (due to lack of efficacy or safety) to canakinumab (4 mg/kg every 4 weeks) and were hospitalized at the rheumatology department from August 2012 to July 2020 were included. Primary efficacy outcomes were 30% or greater improvement based on the paediatric criteria of the American College of Rheumatology (ACR30), achievement of inactive disease (JADAS 71 =0) and clinical remission (ACR sJIA clinical inactive disease criteria). Follow-up from time first canakinumab dose administered was 12 months or the closest time point (not less than 6 and not more than 18 months). Data were extracted from electronic outpatient medical records. During the study period, 46 patients with sJIA switched from tocilizumab to canakinumab. Median age at baseline was 8.2 (interquartile range [IQR] 4.0–12.9) years, with the median sJIA duration being 1.8 (IQR 0.8–5.8) years; 37 (80%) patients received at least one conventional DMARD (cDMARD; oral corticosteroids, methotrexate and/or cyclosporine A). Study outcomes were followed up in 45 patients (one patient did not attend the follow-up for an unknown reason); median follow-up was 359 (95% confidence interval [CI] 282–404) days. During the follow-up, 1 patient discontinued canakinumab due to tuberculosis detection and the dose was reduced or the injection interval increased in 4 (9%) patients. In total, 27 (60%) patients continued to receive at least one cDMARD. Improvement according to the ACR30 criteria was achieved in 43 patients (96%; 95% CI 85–99), inactive disease in 42 (93%; 95%CI 82–98), and remission in 37 (82%; 95% CI 69 91); after adjustment for actual time-at-risk, the rates were 83, 85 and 73 events per 100 person-years, respectively. During follow-up, 23 AEs (most frequently infections) were reported in 19/45 (42%) patients; 5/45 (11%) patients developed macrophage activation syndrome, with a favorable outcome in all cases. One-year canakinumab therapy was found to be potentially effective as second-line biologic therapy after discontinuation of tocilizumab in patients with sJIA.